LEARNING STRATEGIES: AN STEP TOWARDS REACHING AN EFFECTIVE INFORMATION PROCESS - Pizano Chávez, Guillermina (2014)
This article is shown as an integrated axis which refers directly to the action of strategies in processing the information in the human brain. The objective of this article is to study the achievements of learning strategies influence over the information process, to know the learning process of people in general and to design intervention techniques in order to improve the information process. Therefore, by applying the correct strategies, we will improve any learning process in many ways. From our perspective, to act strategically before any teaching- learning activity involves to make consciously the right decisions in order to regulate the conditions that define the learning process and to reach determined objectives. To teach strategies to students implies to teach them to decide consciously all actions they will perform and to modify them in order to reach determined goals. Results will show us how they are working their abilities, skills and the resources they are working with in their information process. Besides, these results will reveal as well how to improve the gaps in their information process by applying ACRA: Acquisition, Codification, Recovering and Supportive Strategies Scale. According to this scale, brain functions basically with three cognitive basic processes: acquisition, codification and recovery processes. In order to have an excellent cognitive performance, it is necessary to count with metacognitive strategies which Dansereau called Supportive Strategies.